Investigation of a small scale process for preparing fried corn chips - Lee, Chee Siong; Jindal, Vinod Kumar; Kim, Kong-Hwan; Mol, J.J.; Samorn Muttamara; Government of Japan (Bangkok : Asian Institute of Technology, 1983)
This study to investigate a small-scale process for preparing the fried corn chips indigenously. The proposed process consisted of first preparing the first preparing the gelatinized corn flour and then forming the dough by adding the water, starch and salt suitably. Finally the chips were produced by low pressure extrusion of the dough and deep fried in vegetable oil. The experimental corn chips were of highly acceptable quality. A detailed investigation of the processing conditions influencing the corn chips' quality was carried out subsequently. The boiling of raw corn and its subsequent drying distinctly affected in the physical properties of the gelatinized flour, dough and the fried chips. A boiling time of about 10 minutes followed by drying at 80 c̕ showed a good compromise. Dough moisture affected the force required to form the raw chips and the quality of fried chips. Based on overall considerations, 50 percent moisture content of the raw chips appeared to be satisfactory. The addition of starch resulted in the fried chips with smooth texture. The starch content of about 5 percent was to be adequate. Though longer frying times produced chips with lower moisture content a frying time of 2.5 min was found to be most satisfactory for chips with initial moisture of 50 percent.
A thesis submitted in partial fulfillment of the requirements for the degree of Master of Engineering, School of Environment, Resources and Development
Thesis (M.Eng.) - Asian Institute of Technology, 1983
Keywords: Food industry and trade; Corn as food